Simulation and optimization of silicon carbide metal oxide semiconductor field effect transistors - Zhu,Taolue (Nanyang Technological University, 2020)
Silicon carbide (SiC), due to its large band gap, high critical breakdown electric field, carrier saturation velocity and thermal conductivity, has been the best choice of material for the fabrication of high power, high temperature and high frequency semiconductor devices. SiC can also be processed to grow a layer of high-quality thermal oxide (SiO2) to form the metal-oxide-semiconductor field effect transistor (MOSFET), which is the most common semiconductor device structure currently used in power devices. As a variation of MOSFET and a promising power device structure, vertically diffused MOS (VDMOS) has the ability of blocking high voltage and conducting large current using an integrated vertically grown structure. Therefore, there is an intense interest in the study of SiC VDMOS device as it combines the best device design with the attractive semiconductor material properties of SiC.